2021
DOI: 10.1021/acs.molpharmaceut.1c00473
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Site-Specific Conjugation Platform to Improve the Pharmacokinetics and Therapeutic Index of Antibody–Drug Conjugates

Abstract: To overcome a lack of selectivity during the chemical modification of native non-engineered antibodies, we have developed a technology platform termed “AJICAP” for the site-specific chemical conjugation of antibodies through the use of a class of IgG Fc-affinity reagents. To date, a limited number of antibody–drug conjugates (ADCs) have been synthesized via this approach, and no toxicological study was reported. Herein, we describe the compatibility and robustness of AJICAP technology, which enabled the synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 31 publications
3
66
1
Order By: Relevance
“…T-DM1 was found to be relatively stable at lower temperatures (<4 °C) [11,15]. At room temperature or higher, the aggregation percentage increased significantly; however, in the current study, trastuzumab-AJICAPmaytansinoid showed more resistance to high temperature than T-DM1.…”
Section: Gram-scale Preparation and Analysis Of Trastuzumab-ajicap-ma...contrasting
confidence: 59%
See 2 more Smart Citations
“…T-DM1 was found to be relatively stable at lower temperatures (<4 °C) [11,15]. At room temperature or higher, the aggregation percentage increased significantly; however, in the current study, trastuzumab-AJICAPmaytansinoid showed more resistance to high temperature than T-DM1.…”
Section: Gram-scale Preparation and Analysis Of Trastuzumab-ajicap-ma...contrasting
confidence: 59%
“…In order to provide a TI comparison between AJICAP-ADCs and traditional ADCs in the market, we decided to demonstrate the rat toxicology study of trastuzumab-AJICAP-maytansinoid (DAR = 2) as compared to commercially available T-DM1 (DAR = 3.4). The combination of this safety study and a previously reported efficacy study enables comparison of the TI, thereby resulting in a wide enhancement of TI by AJICAP technology [15]. To supply a sufficient quantity of trastuzumab-AJICAPmaytansinoid, gram-scale ADC preparation was also performed, thus, supporting the robustness of the previously established conjugation process [13].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Furthermore, a comparison of the biological properties of ADCs is critical information to be applied for biopharmaceutics. Very recently, our group reported biological studies of maytansinoid-ADCs [ 10 ] and MMAE-based ADCs [ 30 ] derived from the same antibody by cysteine conjugation chemistry. And further comparison studies including physiological analysis are ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that continuous-modemediated ADCs have no significant difference in relative monomer amounts before and after conjugation (less than 1%; data not shown). Detailed analytical comparisons, such as peptide mapping 25 and in vitro/in vivo biological assays, 26 to measure functional activity between batch-synthesized and continuous-process-synthesized ADCs are underway.…”
mentioning
confidence: 99%